Association between α-klotho levels and adults with COPD in the United States - Yan, Dan (Frontiers in Medicine, 2024)
Purpose: Chronic obstructive pulmonary disease (COPD) is accompanied by increased inflammation, persistent lung function decline, and extensive lung injury. Klotho, a wellknown antiaging protein, has anti-inflammatory and antioxidative effects. However, the effects of klotho on COPD have yet to be thoroughly elucidated. This study examined the association among COPD adults and their α-klotho level.Patients and methods: Data were collected from the 2007 to 2012 National Health and Nutrition Examination Survey (NHANES). A total of 676 participants were analysed and divided into COPD (n=403) and non-COPD (n=273) groups. The two groups were compared with respect to clinical characteristics. Logistic regression analysis and a generalized additive model were used to estimate the association between COPD incidence and serum α-klotho concentration. All COPD participants were stratified according to the levels of α-klotho (Q1: <687 pg/ml; Q2: 687-900 pg/ml; Q3: ≥900 pg/ml), and clinical characteristics were compared.Results: Non-COPD individuals had higher α-klotho levels than did COPD individuals (863.09 ± 267.13 vs. 817.51 ± 302.20, P<0.05). Logistic regression analysis revealed that the Q2 and Q3 layers had a lower risk of COPD than did the Q1 layer, with odds ratios (ORs) of 0.73 (0.50, 0.99) for Q2 and 0.58 (0.41, 0.86) for Q3 (p < 0.001). The generalized additive model showed that the risk of COPD gradually decreased with increasing α-klotho concentration when the α-klotho concentration < 1500 pg/ml, while the risk of COPD increased as the α-klotho concentration increased to ≥1500 pg/ml. Compared with individuals in the Q2 or Q3 groups, individuals with COPD in the Q1 group were more likely to be current smokers, have lower levels of erythrocytes, and have higher levels of creatinine and leukocytes.Increased α-klotho levels were negatively correlated with the risk of COPD in participants over 40 years old with α-klotho <1500 pg/ml. When α-klotho was ≥1500 pg/ml, the risk of COPD increased as α-klotho levels increased. Pulmonary ventilation function and the number of haemocytes differed among COPD patients with different levels of αklotho.